Consent to sexual activity in accordance with article 197 of the Criminal Code (Ius Novum, 2024)
In the 21st century, legislation in many jurisdictions is moving away from defining the crime of rape based on the use of coercion and instead focusing on the violation of the injured person’s will. This analytical article aims to highlight changes in the understanding of the features of a crime under Article 197 of the Criminal Code, aligning it with the current societal awareness and views. This issue is relatively absent in scientific discourse, likely because phenomena such as stealthing have only recently received attention. The authors posit that, given the current interpretation of the features of the crime of rape in both doctrine and case law, the present legal framework satisfies the criteria of Article 36 of the Istanbul Convention. However, the doctrine, jurisprudence, and potentially the legislator face the challenge of adapting the crime of rape to contemporary needs. The conclusions drawn from the conducted research reveal problems that are only briefly touched upon in criminal law literature.
Keywords: rape, consent, criminal law, sexual crimes, stealthing